Fire Disaster and Its Implications on Survivors and Social Work Practice: The Case of Rumah Lepang Sayat, Engkilili - Daphne Tala, Jusin; Dolly, Paul Carlo (UNIMAS, 2020)
This paper focuses on the implications of a longhouse fire on its survivors. It also presents the assistance that survivors received during post-disaster and the implications on the social work practice. It draws on qualitative research based on in-depth interviews with survivors selected through purposive sampling. The data of the study were analysed based thematic analysis. The findings revealed that the survivors faced both short-term and longterm implications after the fire disaster. The assistance received was mainly focused on responding to the shortterm implications and was less focused on long-term implications. In the scheme of things, these implications bear on the social work practices as well as on the conditions of the fire disaster survivors.